Is human immunodeficiency virus a risk factor for the development of nonunion?—a case–control study. Issue 2 (16th June 2023) - Graham, Simon Matthew; Maqungo, Sithombo; Laubscher, Maritz; Ferreira, Nando; Held, Michael; Harrison, William James; Simpson, A. Hamish; MacPherson, Peter; Lalloo, David G.
Abstract: Objective: Human immunodeficiency virus (HIV) infection has been suggested to be associated with an increased risk of the development of nonunion after a fracture. This prospective matched case–control study in South Africa investigated common risk factors, including HIV status, that influence the development of a nonunion after a femur or tibia fracture. Methods: Adult participants (cases) with established nonunions of the femur or tibia shaft were recruited over a 16-month period, between December 2017 and April 2019. They were matched for (1) age; (2) sex; (3) fracture site; and (4) fracture management type, with "control" participants who progressed to fracture union within 6 months of injury. All participants were tested for HIV. Multivariable logistic regression models were constructed to investigate associations between known risk factors for the development of nonunion and impaired fracture healing. Results: A total of 57 cases were matched with 57 "control" participants (44/57 male, 77.2% vs. 13/57 female, 22.8%, median age 36 years). HIV status was not associated with the development of nonunion after the management of tibia and femur fractures, on both univariate (odds ratio, 0.40; confidence interval, 0.10–1.32; P = 0.151) or multivariable (odds ratio, 0.86; confidence interval, 0.18–3.73; P = 0.831) analysis. No other confounding factors were shown to have any statistically significant impact on the odds of developing nonunion in this study cohort. Conclusion: This study demonstrates that HIV does not seem to increase the risk of the development of nonunion and HIV-positive individuals who sustain a fracture can be managed in the same manner as those who are HIV negative.